Evaluation of the performance of bio-oil obtained through pyrolysis of coffee waste - Figueiredo, Monique Kort-Kamp; Caldas, Karolyne Nogueira de Castro; Nascimento, Beatriz Pereira do; Schroeder, Priscila; Romeiro, Gilberto Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Bio-oils are a complex blend of organic compounds formed by fragmentation of the structures present in biomass after undergoing a thermal process known as pyrolysis. Coffee waste is an organic residue discarded in large quantities in Brazil. This work aimed to evaluate some chemical and physicochemical characteristics of this oil, to seek economically viable uses for the product. Five pyrolysis procedures were employed and an average bio-oil yield of 18% was obtained. The oil was subjected to tests such as infrared, pour point and ash content. Infrared spectroscopy revealed an intense aliphatic character of the structure, which also had considerable presence of oxygen due to the presence of functional groups such as carbonylates, carboxylates, esters, ketones, amides and ether, as well as aromatics. The pour point determined for the bio-oil was 20° C and the ash content was less than 1%.